Implementasi Hak Restitusi Terhadap Korban Tindak Pidana Perdagangan Orang - Annisa Novianti; Frimer, Teno (Lareh Law Review, 2024)
Restitution can be interpreted as the right of victims of criminal acts provided by the perpetrators or third parties as a form of loss recovery and legal protection for victims, which can be in the form of compensation for material and/or immaterial losses suffered. The implementation of the right to restitution for victims of trafficking in persons can not only be carried out on the basis of statutory orders but also requires the role of both law enforcement officials and other non-governmental organizations. The provision of restitution rights as a form of legal protection can be seen in several court decisions, but in fact this is very rarely found in the jurisdiction of the Padang District Court Class I A. The formulation of the problem is: 1. How is the implementation of the provision of restitution to victims of human trafficking crimes, 2. what are the obstacles faced by law enforcement, 3. and how is the solution to the obstacles in implementing the provision of restitution to victims of human trafficking crimes in the jurisdiction of the Padang District Court Class 1 A? This research uses empirical juridical methods with the aim of studying and analyzing the procedures for the operation of law in community life. From the results of this research, the implementation of restitution rights in the jurisdiction of the Padang District Court is still not optimal. This is because there are several obstacles such as the long mechanism for submitting restitution requests, the absence of demands regarding restitution rights included in the verdict and also the lack of socialization of restitution rights. The obstacles faced require solutions such as simplifying the procedural system for applying for restitution rights, increasing attention to the interests of victims and increasing the socialization of the right to restitution itself, both from victims, the community and even law enforcement officials. Keywords : Human Trafficking, Restitution Rights, Victims